In-situ AFM and quasi-in-situ studies for localized corrosion in Mg-9Al-1Fe-(Gd) alloys under 3.5 wt.% NaCl environment - Shen, Junping (2023)
Revealing the localized corrosion process of Mg alloy is considered as one of the most significant ways for improving its corrosion resistance. The reliable monitor should be high distinguishability and real-time in liquid environment. Herein, Mg-9Al-1Fe and Mg-9Al-1Fe-1Gd alloys were designed to highlight the impact of intermetallic on the corrosion behaviour. In-situ AFM with a special electrolyte circulation system and quasi-in-situ SEM observation were used to monitor the corrosion process of the designed alloys. SEM-EDS and TEM-SAED were applied to identify the intermetallic in the designed alloys, and their volta potentials were measured by SKPFM. According to the real-time and real-space in-situ AFM monitor, the corrosion process consisted of dissolution of anodic α-Mg phase, accumulation of corrosion products around cathodic phase and shedding of some fine cathodic phase. Then, the localized corrosion process of Mg alloy was revealed combined with the results of the monitor of corrosion process and Volta potential difference.